Analyzing the Narrative in the Game of Motlotlo to Better Understand the Relationship that Customers have with Product Brands - Makhafola, Kelebogile (The IIE, 2015)
The game Motlotlo is not only a storytelling game exploring the significant moments in the tellers life, the game has the opportunity to decode consumer perception of consumers in a manner that brings forward the external brand story. In contextualizing the game, the research process seeks out the degree in which brand association is informed by experiential and collective memory, and further more unpack how word of mouth communication (such as in the game) has an impact on building or breaking perception. The paper aims to analyse the content of consumer stories to further understand the relationship between consumers and product brands. Thus Motlotlo becomes a tool which may be used to analyse brand contact points and consumer relationship key points. The paper aims to seek how the game can be used for brand analysis platforms such as healthy brand audits, brand score cards and report cards.
Keywords: Motlotlo; Brand Analysis; Consumer Behaviour; Story Telling; Communication